The health behaviour of black insulin dependent diabetic patients - G.L. Xaba; S.R. Dewar (AOSIS, 1991)
This descriptive retrospective study explores the perceptions and experiences relating to their discease of 20 adult Black insulin - dependent diabetic clients in terms of Cox's Interaction Model of Client Health Behaviour. Cognitive and affective responses were investigated by means of structured interviews. Questionnaires completed by 30 registered nurses examined by their impressions of diabetic patients' motivation and levels of satisfaction with their care. Findings are discussed and recommendations made.